Effect of Ultrafine Powderization and Solid Dispersion Formation via Hot-Melt Extrusion on Antioxidant, Anti-Inflammatory, and the Human Kv1.3 Channel Inhibitory Activities of Angelica gigas Nakai - Yunyao Jiang; Jingpei Piao; Nan Liu; Jincai Hou; Jianxun Liu; Weicheng Hu (Bioinorganic Chemistry and Applications)
Angelica gigas Nakai (AGN) was first processed by ultrafine grinding technology and hot-melt extrusion (HME). The potential antioxidant and anti-inflammatory activities of AGN with a different process were compared, and the effect on the human Kv1.3 potassium channel was detected. The process of ultrafine powderization on AGN significantly increased the total phenolic and flavonoid contents, antioxidant activity, and DNA damage protective effect. On the contrary, AGN solid dispersion (AGN-SD) based on Soluplus® showed the highest inhibitory effect on NO production and the human Kv1.3 channel. In addition, AGN-SD inhibited the production of prostaglandin E2 and intracellular reactive oxygen species and the mRNA expression of inducible nitric oxide synthase, cyclooxygenase-2, interleukin 1β, and interleukin 6. Taken together, these results suggest that ultrafine powderization and solid dispersion formation via HME can significantly improve the biological activities of AGN. The results also suggested that ultrafine powderization and HME may be developed and applied in the pharmaceutical industry.